Synthesis and Characterization of 1-Substituted-3,5-Diaryl-4-Bromo Pyrazoles - Jamode, V.S.; Jawanjal, S.D. (Asian Journal of Chemistry, 2010)
1-(2-Hydroxy-3,5-dichloro phenyl)-3-aryl-2-bromo propan-1,3-diones are prepared by the action of bromine on 1-(2-hydroxy-3,5-dichloro phenyl)-3-aryl propan-1,3-diones. 3,5- Diaryl-1- substi- tuted-4-bromo pyrazoles have been synthesized by refluxing 1-(2-hydroxy- 3,5-dichloro phenyl)-3-aryl-2-bromo propan-1,3-diones with nucleophile such as isonicotinic acid hydrazide, semicarbazide, thiosemicarbazide in ethyl alcohol for about 2.5 h in basic medium. The structures of these compounds have been characterized by spectral analysis. Purity of the synthesized heterocycles was checked by TLC.